Mowat-Wilson'S Syndrome: A Case Report (2012)
Mowat-Wilson syndrome (MWS) is a very infrequent congenital polimalformative disorder, caused by mutations, deletions or insertions of the ZEB2 gene, which codify for a protein that is involved in the migration of the neural crest cells and the development of middle line structures. The inheritance pattern is autosomal dominant, haplo-insufficient.